RANCANG BANGUN KIT INSTALASI LISTRIK UNTUK MEDIA PEMBELAJARAN MATA KULIAH INSTALASI LISTRIK - Monitasari, Anna; Usrah, Ifkar; Aripin, Aripin (Teknik Elektro Universitas Siliwangi, 2022)
According to the syllabus of electrical installation courses lectures are carried out face-to-face theory and practicum. The number of practicums that must be met for this course is seven practicums. Currently the facilities for seven practicum electrical installation courses are not yet available in the laboratory of Electrical Engineering Faculty of Engineering Siliwangi Unive rsity and carried out practicumnya in The State Polytechnic of Bandung. To carry out practicum in the laboratory of Electrical Engineering Power System Siliwangi University, it is necessary to create learning media for the course prakitkum electrical installation. One form of learning media is the Integrated Instrument Component (KIT) practicum of electrical installation for one -phase power measurement. Kit Installation Components consist of Miniature circuit breaker (MCB), contact box, single switch, double switch, series switch, exchange switch, lamp fitting, and lamp. The measurement tool component consists of PZEM-004T sensor, liquid crystal display (LED), arduino uno, and push button. Research methods are experimental methods and documentation methods. This research consists of making KIT and circuit design, component collection, designing kit components and microcontrollerprogramming, component maintenance, circuit check with multimeter. Voltage, power factor, and frequency values are measured to determine the feasibility of kit practicum. The test result data shows that at a frequency of 50 Hz the voltage range is measured from 228.1/230.7 Volts, load power factor 1 for resistive loads, power factor 0.65 for inductive loads. The results are in accordance with the data of The Indonesian National Standard (SNI 04-0227-2003). This means that the practicum kits are made worth using for practicum electrical installation courses. Keywords : PZEM-004T sensor, electrical installation, Learning Media